An assessment of physiological and health responses in Catla catla fingerlings after polystyrene microplastic exposure - Eram Rashid; Syed Makhdoom Hussain; Shafaqat Ali; Dariusz Kucharczyk; Joanna Nowosad; Khalid A. Al-Ghanim; Nadia Nazish (Scientific Reports)
Abstract Microplastics (MPs) form when plastic debris is released into the aquatic environment, where they decompose and have deleterious effects on aquatic life. This study aimed to examine the harmful impacts of polystyrene MPs (PS-MPs) on the growth, carcass composition, hematology, digestibility, histopathology, and mineral analysis of Catla catla (11.09 ± 0.09 g/fish). Six experimental diets were prepared using canola meal (CM) as the base, each containing varying levels of PS-MPs: a control diet without MPs, and diets with 0.5%, 1%, 1.5%, 2%, and 2.5% PS-MPs. For ninety days, three groups of 15 fingerlings each were fed the test diets at a rate of 5% of their live, wet body weight. The growth rate and feed intake of C. catla fish showed a significant decline after the exposure to the diet containing 2.5% PS-MPs. Dietary inclusion of 2.5% PS-MPs resulted in reduced weight gain (g) and increased FCR. Mineral content and nutritional digestibility declined as PS-MP levels rose. PS-MPs led to a decrease in ash and protein content, while causing an increase in moisture levels and body fat. Moreover, exposure to PS-MPs resulted in significant reduction in RBCs, PLT, Hb, PCV, and MCHC, while WBCs, MCH, and MCV showed substantial increases. The histological analysis of the gut revealed elevated intestinal irregularities at 2.5% PS-MPs level. Notably, the present study revealed that PS-MPs accumulate in the gut, compromising the nutritional quality and overall well-being of C. catla fingerlings.